2020
DOI: 10.21203/rs.3.rs-136057/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delivery of Melittin Loaded Niosomes for Breast Cancer Treatment: an in-vitro and in-vivo Evaluation of Anti-cancer Effect

Abstract: BackgroundMelittin, a peptide component of honey bee venom, is an appealing candidate for cancer therapy. In the current study, Melittin and Melittin loaded niosome had been optimized and assessed the anticancer effect an In-Vitro on 4T1 and SKBR3 breast cell lines and In-Vivo on BALB/C inbred mice. "Thin-layer hydration method" was used for preparing the Niosomes; different niosomal formulations of Melittin were prepared and characterized in terms of morphology, size, Polydispersity index, encapsulation effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Bee venom was administered to breast cancer cells in six studies [ 19 , 20 , 21 , 22 , 23 , 24 ], whereas melittin or processed melittin was administered to breast cancer cells in seven studies [ 20 , 21 , 22 , 25 , 26 , 27 , 28 ]. Among them, three studies compared the results of melittin and bee venom administration [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bee venom was administered to breast cancer cells in six studies [ 19 , 20 , 21 , 22 , 23 , 24 ], whereas melittin or processed melittin was administered to breast cancer cells in seven studies [ 20 , 21 , 22 , 25 , 26 , 27 , 28 ]. Among them, three studies compared the results of melittin and bee venom administration [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was only one study on phospholipase A2 from bee venom [ 29 ]. All studies, except one, attempted to confirm the results according to the dose [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 29 ]. On the other hand, three studies confirmed the results according to the duration of administration [ 22 , 23 , 26 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…AFM samples were prepared by placing 5μl of diluted niosomes on 1cm 2 glass slides and left to dry at room temperature. Prepared samples were visualized with a Nanowizard II atomic force microscope (JPK Instruments, Berlin, Germany) with a low-stress silicon nitride cantilevers (AppNano, USA) using AC mode at 66k Hz scan [17,18] .…”
Section: Morphologymentioning
confidence: 99%
“… 16 Niosomes are biocompatible bilayer structures formed by the self-organization of nonionic surfactants and cholesterol that can overcome drawbacks associated with liposomes such as poor biocompatibility, low chemical stability, short storage life, and difficult large-scale production. 17 , 18 Niosomes have gained much attention in drug delivery systems because of their unique properties, including exceptional biocompatibility, biodegradability, stability, nonimmunogenicity, and the ability to encapsulate both hydrophilic and hydrophobic drugs. 19 21 Although vesicular systems like niosomes have special potential in cancer drug delivery, they still suffer from short blood circulation time and fast elimination by the reticuloendothelial system (RES).…”
Section: Introductionmentioning
confidence: 99%